Neuropathology and Neurochemistry of Nonmotor Symptoms in Parkinson's Disease - Isidro Ferrer (Parkinson's Disease, 2011)
Parkinson disease (PD) is no longer considered a complex motor disorder characterized by Parkinsonism but rather a systemic disease with variegated non-motor deficits and neurological symptoms, including impaired olfaction, autonomic failure, cognitive impairment, and psychiatric symptoms. Many of these alterations appear before or in parallel with motor deficits and then worsen with disease progression. Although there is a close relation between motor symptoms and the presence of Lewy bodies (LBs) and neurites filled with abnormal 𝛼-synuclein, other neurological alterations are independent of the amount of 𝛼-synuclein inclusions in neurons and neurites, thereby indicating that different mechanisms probably converge in the degenerative process. Involvement of the cerebral cortex that may lead to altered behaviour and cognition are related to several convergent factors such as (a) abnormal 𝛼-synuclein and other proteins at the synapses, rather than LBs and neurites, (b) impaired dopaminergic, noradrenergic, cholinergic and serotoninergic cortical innervation, and (c) altered neuronal function resulting from reduced energy production and increased energy demands. These alterations appear at early stages of the disease and may precede by years the appearance of cell loss and cortical atrophy.